2020
DOI: 10.1038/s41598-020-68792-8
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril-associated glycoprotein 4 (Mfap4) regulates haematopoiesis in zebrafish

Abstract: Microfibril-associated glycoprotein 4 (MFAP4) is an extracellular matrix protein belonging to the fibrinogen-related protein superfamily. MFAP4 is produced by vascular smooth muscle cells and is highly enriched in the blood vessels of the heart and lung, where it is thought to contribute to the structure and function of elastic fibers. Genetic studies in humans have implicated MFAP4 in the pathogenesis of Smith-Magenis syndrome, in which patients present with multiple congenital abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
(105 reference statements)
1
11
0
Order By: Relevance
“…Also, a macrophage-specific gene aconitate decarboxylase 1, acod1 (also known as immunoresponsive 1 homolog, irg1), which is known to be highly expressed under bacterial infections and to be important for the production of reactive oxygen species by macrophages [70,71], was among the most induced genes in pneumococcal infection. Moreover, consistent with the previous studies on Staphylococcus epidermis-responsive genes in zebrafish, two duplicates of the gene microfibril associated protein 4 (mfap4.5 and mfap4.2), a well-known macrophage marker shown to promote macrophage differentiation during hematopoiesis in zebrafish [72,73], were also upregulated upon infection. Of note, while not quite reaching the cutoff levels set for the induced genes, the induction of the genes for common pro-inflammatory cytokines Il1b (4.4-fold induction) and Il6 (9.9-fold induction) was also evident, with mean normalized read counts of 14 and 4.6 in challenged larvae, and 3 and 0.3 in unchallenged larvae, respectively.…”
Section: Plos Geneticssupporting
confidence: 89%
“…Also, a macrophage-specific gene aconitate decarboxylase 1, acod1 (also known as immunoresponsive 1 homolog, irg1), which is known to be highly expressed under bacterial infections and to be important for the production of reactive oxygen species by macrophages [70,71], was among the most induced genes in pneumococcal infection. Moreover, consistent with the previous studies on Staphylococcus epidermis-responsive genes in zebrafish, two duplicates of the gene microfibril associated protein 4 (mfap4.5 and mfap4.2), a well-known macrophage marker shown to promote macrophage differentiation during hematopoiesis in zebrafish [72,73], were also upregulated upon infection. Of note, while not quite reaching the cutoff levels set for the induced genes, the induction of the genes for common pro-inflammatory cytokines Il1b (4.4-fold induction) and Il6 (9.9-fold induction) was also evident, with mean normalized read counts of 14 and 4.6 in challenged larvae, and 3 and 0.3 in unchallenged larvae, respectively.…”
Section: Plos Geneticssupporting
confidence: 89%
“…When comparing clusters 0‐2 alone, each cluster was characterized by a small number of DEGs (47, 107, and 112 genes, respectively; Table S5, Figure S3A). The DEGs of cluster 1 included dermatopontin ( DPT ; Figure 4) and microfibril associated protein 4 ( MFAP4 ) gene, both of which were important for stem cell niche 25,26 . Cluster 2 was characterized by fibrillin 1 ( FBN1 ), serpin family E member 2 ( SERPINE2 ), integrin subunit beta like 1 ( ITGBL1 ), PDZ and LIM domain 5 ( PDLIM5 ), and filamin A ( FLNA ).…”
Section: Resultsmentioning
confidence: 99%
“…The DEGs of cluster 1 included dermatopontin (DPT; Figure 4) and microfibril associated protein 4 (MFAP4) gene, both of which were important for stem cell niche. 25,26 Cluster 2 was characterized by fibrillin 1 (FBN1), serpin F I G U R E 1 Identification of human adipose mesenchymal stem cells (hAMSCs). A, hAMSCs are characterized with five surface markers showing the potential of HSC to differentiate toward adipocytes (B) and osteocytes (C and D).…”
Section: Heterogenetic Expression Pattern and Clusters In Hamscsmentioning
confidence: 99%
“…Therefore, abnormal cell migration and invasion are important for the pathogenesis of EMS. MFAP4, a member of the extracellular matrix, acts as a ligand and participates in the recognition of adhesion and biochemical interactions between cells, as well as in the formation of elastic fibers ( 31 ). Studies have shown that the upregulation of MFAP4 can inhibit the effect of miRNA (Mir)-147b on cell malignant invasiveness ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%